Depletion of Natural Resources and Its Impact on Pakistan Economy (Journal of Asian Development Studies, 2025)
Depletion of natural resources is a major obstacle to sustainable economic development, particularly in resource-deficient developing economies like Pakistan. In this research, the authors discuss the scale, causes, and economic consequences of natural resource depletion in Pakistan, particularly in the agriculture and industry sectors. We used a mixed-methods design to analyze a time-series dataset spanning 1998 to 2021. Three major hypotheses were evaluated: (i) the resource-economy nexus, (ii) demographic pressures, and (iii) institution effectiveness. Descriptive and trend analyses reveal significant declines in per capita water availability and increased volatility in sectoral GDP. According to econometric estimates, the positive and significant relationship between water availability and the agricultural share of GDP was observed, and the negative link between natural gas supply and the industrial share of GDP was found. Population growth negatively affects GDP growth and job opportunities. A negative association was identified between waterscarcity and GDP growth. The empirical findings support all hypotheses; specifically, population growth and urbanization have a significant negative impact on growth. The study therefore proposes that policymakers focus on integrated resource management, investment in green technologies, environmental governance, and strategic demographic planning